ответ:А (-1, -1, -1), В (-1, 3, -1), С (-1, -1, 2)
AB=\sqrt{\big(x_B-x_A\big)^2+\big(y_B-y_A\big)^2+\big(z_B-z_A\big)^2}==\sqrt{\big(-1-(-1)\big)^2+\big(3-(-1)\big)^2+\big(-1-(-1)\big)^2}==\sqrt{0+4^2+0}=4
CB=\sqrt{\big(x_B-x_C\Big)^2+\big(y_B-y_C\big)^2+\big(z_B-z_C\big)^2}==\sqrt{\big(-1-(-1)\big)^2+\big(3-(-1)\big)^2+\big(-1-2\big)^2}==\sqrt{0+16+9}=5
AC=\sqrt{\big(x_C-x_A\big)^2+\big(y_C-y_A\big)^2+\big(z_C-z_A\big)^2}==\sqrt{\big(-1-(-1)\big)^2+\big(-1-(-1)\big)^2+\big(2-(-1)\big)^2}==\sqrt{0+0+3^2}=3
P_{\Delta ABC}=AB+CB+AC=4+5+3=12boxed{\boldsymbol{P_{\Delta ABC}=12}}
Объяснение:
ответ: угол 2 = А = 60, значит угол В= 180-60=120
Угол АВN=KBC = 180 - (60+90)=30
УГОЛ 1 = угол В - (30+30)= 120 - 60=60
ответ 60
Объяснение: